Shakespeares Paradox - Saks , Sarah-Lizzie (Tidskrift för genusvetenskap, 1997)
Starting with four postulates, this artide (somewhat sweepingly) demonstrates how the paradox of Shakespeare, the discrepancies of his time, become our paradox and our discrepancies. So have for instance the young Elizabethan gallants been replaced by "the middleaged woman". Institutionalized theatre is part of the patriarchal tradition. Creativity and flexibility is mostly found within free theatre groups. Burning issues pertaining to the theatre tend to be the same over the centuries; what was passionately discussed during Elizabethan times is still being discussed, albeit with a different slant. Although the tone superficially can sound different, it is the same conventions and implications, political as well as artistical, that are discussed.